Copyright in the creative industries: Protection of graphic design and illustration - Siregar, Bismar (Journal of Law Science, 2025)
Copyright is a type of intellectual property right that must be respected. Intellectual Property Rights are exclusive (special) rights owned by creators/inventors as a result of intellectual activity and creativity that iis unique and new. Graphic Design Digital illustration, even though it is a form of work and therefore protected by copyright, remains an easy target for copyright violations, both economic rights violations such as buying and selling works, using works to add aesthetic value to goods for sale, or moral irights violations such as modifying without permission or even recognizing the work as one's own. This copyright violation does not just happen, but there iare factors that encourage it, including a habit/tradition (cultural aspect); seeking profit (economic aspect); low understanding of copyright; low implementation of sanctions (juridical aspect); and periodic raids are not implemented. Regulations regarding the legal protection of copyright in Indonesia are regulated in Law Number 28 of 2014 concerning Copyright which directly provides legal protection for creators of graphic design and illustration iworks and in protecting their creations, creators of graphic designs and illustrations can take legal action, both preventive and repressive.